Hiv-1 central nervous system compartmentalization and cytokine interplay in non-subtype B Hiv-1 infections in Nigeria and Malawi (2020)
"HIV-1 compartmentalization in the central nervous system (CNS) and its contribution to neurological disease have been well documented. Previous studies were conducted among people infected with subtypes B or C where CNS compartmentalization has been observed when comparing viral sequences in the blood to virus in cerebrospinal fluid (CSF). However, little is known about CNS compartmentalization in other HIV-1 subtypes. Using a deep sequencing approach with Primer ID, we conducted a cross-sectional study among Nigerian and Malawian HIV-1 cohorts with or without fungal Cryptococcus infection diagnosed as cryptococcal meningitis (CM) to determine the extent of CSF/CNS compartmentalization with CM. Paired plasma and CSF samples from 45 participants were also analyzed for cytokine/chemokine levels. Viral populations comparing virus in the blood and the CSF ranged from compartmentalized to equilibrated, including minor or partial compartmentalization or clonal amplification of a single viral sequence. The frequency of compartmentalized viral populations in the blood and CSF was similar between the CM- and CM+ participants. We confirmed the potential to see compartmentalization with subtype C infection and have also documented CNS compartmentalization of an HIV-1 subtype G infection. Cytokine profiles indicated a proinflammatory environment, especially within the CSF/CNS. However, sCD163 was suppressed in the CSF in the presence of CM, perhaps due to elevated levels of IL-4, which were also a feature of the cytokine profile, showing a distinct cytokine profile with CM.